Strategi Partai Koalisi dalam Pemenangan AW Nofiadi Mawardi – Ilyas Panji Alam pada Pemilihan Kepala Daerah Kabupaten Ogan Ilir Tahun 2015 - Ahmad Syukri; Ricky Meilandi (Universitas Islam Negeri Raden Fatah Palembang, 2018)
This research related to the Strategic of the political party coalition of the AW Noviandi and Ilyas Panji Alam in the local elections of Ogan ilir Regency 2015. Panji Alam is carried out so that it is able to achieve sound votes that are quite large from the other candidates. Research objects: party administrators involved in the AW Noviandi and Ilyas Panji Alam coalition partners. This research use the theory of Arend Lijphard's political party coalition theory, minimal-winning coalition, minimum range coalition, minimum size coalition, bargaining position, minimal connected winning coalitions, policy- viable coalition and the theory of Peter Schorder The political strategy is divided into two: offensive (attacking) and defensive (defensive) strategies. The offensive strategy is divided into two, namely the strategy to expand the market and strategies to penetrate the market. While the defensive strategy is a strategy to maintain the market. This research is explained in two stages; the process of building coalitions and party considerations in partnership, Strategy of the Carrying Party for the Winning of AW Noviandi Mawardi-Ilyas Panji Alam, Type of descriptive research through a qualitative approach with case study methods of type of field research. Sources of data in this study are parties directly involved in the problems under study. Data was collected by in-depth interview techniques and documentation. Data is analyzed through data reduction, data presentation and conclusion drawing. The results showed that in the victory of Noviandi and Ilyas Panji Alam in the OI 2015 Election could not be separated from the influence of supporting parties which moved party cadres through offensive and defensive political strategies to run well and effectively embrace the community, maintaining the period of permanent voters and seasonal voters.